USING AUTHENTIC LISTENING MATERIALS IN EFL CLASSROOM: STUDENTS’ PERCEPTIONS IN INDONESIAN CONTEXT - Refai Refai (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2018)
Instructing listening comprehension to EFL students need good plannings. Authentic listening materials as a strategic teaching media are best utilized by English instructors to facilitate the EFL students’ listening comprehension in classrooms and language laboratory. Applying authentic listening materials as teaching media in listening practice activites are challenged to bridge EFL students and not only enhancing their listening skill but also improving and developing their knowledge of the real life, culture, and social affairs of English native speakers.The source of authentic listening materials applied in the subject class are mostly taken from youtube.com. A popular open source website which provide online videos. The aim of the study was to find out EFL students’ attitudes and perceptions when and after using the authentic videos in an EFL listening class. The participants of the study were the second semester EFL students of English Language Teaching department in Universitas Muhammadiyah Metro Indonesia. The data were gathered from a questionnaire and open interviews. It is found out that most of EFL students who were instructed by the authentic videos show positive attitudes and have good perceptions in utilizing youtube videos as one of the alternative authentic materials in comprehending English utterances.